William Wordsworth's Poetry. (Reader's Guides., 2010)
William Wordsworth continues to be one of the most popular and widely studied poets from the nineteenth century. This Readers Guide provides an overview of Wordsworths career, which began in obscurity, persisted through ridicule, and culminated finally in popular success and acclaim. It introduces readers to the literary, philosophical, and political contexts crucial to understanding Wordsworths poetry, offering fresh approaches for reading his most important poems in light of recent developments in literary studies while also spotlighting traditional ones. This guide explores the reasons why Wordsworth continues to be the leading figure of British Romantic literature. It is an indispensable guide to studying Wordsworth's poetry, language, contexts and criticism. €